Fabrication and behaviors of CdS on Bi2MoO6 thin film photoanodes. Issue 18 (9th February 2017) - Yang, Hao; Jin, Zhiliang; Hu, Hongyan; Lu, Gongxuan; Bi, Yingpu
Abstract : Most Bi-based photoelectrodes have suitable band gaps and can effectively promote hydrogen evolution from water splitting, but there are few studies up to now for simple preparation methods for Bi-based binary metal oxides as photoanodes. Abstract : Most Bi-based photoelectrodes have suitable band gaps and can effectively promote hydrogen evolution from water splitting, but there are few studies up to now for simple preparation methods for Bi-based binary metal oxides as photoanodes. Here, we prepared a novel Bi2 MoO6 thin film photo-anode without a template; our preparation methods of Bi-based binary metal oxides with controlled morphologies were conducted by growing the Bi2 MoO6 directly on an electrical substrate via an in situ growth process. The photoanodes show well-shaped thin film morphologies and exhibit impressive photoelectrochemical properties compared to the Bi-based photoanodes synthesized by conventional methods. A 2× enhanced photocurrent was obtained when the Bi2 MoO6 thin film photoanodes were modified with CdS in comparison with the primary Bi2 MoO6 (about 0.85 mA cm −2 ) under identical conditions. The enhanced photoelectrochemical properties were studied using several techniques including SEM, XRD, XPS, UV-vis diffuse reflectance, etc. and the results were in good agreement with each other. Moreover, the Bi2 MoO6 thin film photoanodes possess long-term stability under solar irradiation and show a considerable photocurrent.